The New Contours of the Russia‒ Africa Partnership: The Economic, Political, Cultural-Humanitarian and Youth Dimensions - K. A. Aleshin; G. K. Sugakov (Вестник Московского Университета. Серия XXV: Международные отношения и мировая политика)
.